A Review on Utilization of Domestic Waste in Rooftop Vegetable Gardening - Prajapati, Niraj Kumar (Journal of Agricultural Extension Management, 2023)
Populations living in urban and peri-urban areas around the world are increasing rapidly. Rapid urbanisation is placing enormous demand on urban food supply systems and causing problems like a rapid decrease in green space and an increase in heat island effects in urban areas. Rooftop vegetable gardening can reduce the temperature of roofs and the surrounding air, help to lessen the urban heat island effect, and absorb carbon and noise. In some urban rooftop gardens, mineral fertilisers and pesticides are used. Researchers observed that compost can be used as a source of nutrients instead of mineral fertilizers. Moreover, it can control pests, weeds, and diseases; reduce soil erosion; and increase soil moisture content. Kitchen waste compost might be a suitable supplement in rooftop vegetable gardens because domestic garbage is common in every household in urban and peri-urban locations. In India, rooftop gardening is quite a new phenomenon. This review work will help to understand rooftop gardening and conduct research on rooftop gardens in the future